Controlled Delivery of Vancomycin via Charged Hydrogels. - Carl T Gustafson; Felix Boakye-Agyeman; Cassandra L Brinkman; Joel M Reid; Robin Patel; Zeljko Bajzer; Mahrokh Dadsetan; Michael J Yaszemski (PLoS ONE, 2016)
Surgical site infection (SSI) remains a significant risk for any clean orthopedic surgical procedure. Complications resulting from an SSI often require a second surgery and lengthen patient recovery time. The efficacy of antimicrobial agents delivered to combat SSI is diminished by systemic toxicity, bacterial resistance, and patient compliance to dosing schedules. We submit that development of localized, controlled release formulations for antimicrobial compounds would improve the effectiveness of prophylactic surgical wound antibiotic treatment while decreasing systemic side effects. Our research group developed and characterized oligo(poly(ethylene glycol)fumarate)/sodium methacrylate (OPF/SMA) charged copolymers as biocompatible hydrogel matrices. Here, we report the engineering of this copolymer for use as an antibiotic delivery vehicle in surgical applications. We demonstrate that these hydrogels can be efficiently loaded with vancomycin (over 500 μg drug per mg hydrogel) and this loading mechanism is both time- and charge-dependent. Vancomycin release kinetics are shown to be dependent on copolymer negative charge. In the first 6 hours, we achieved as low as 33.7% release. In the first 24 hours, under 80% of total loaded drug was released. Further, vancomycin release from this system can be extended past four days. Finally, we show that the antimicrobial activity of released vancomycin is equivalent to stock vancomycin in inhibiting the growth of colonies of a clinically derived strain of methicillin-resistant Staphylococcus aureus. In summary, our work demonstrates that OPF/SMA hydrogels are appropriate candidates to deliver local antibiotic therapy for prophylaxis of surgical site infection.